Genius and the Mind: Studies of Creativity and Temperament - Steptoe, Andrew (Oxford Oxford University Press, 1998)
What is genius? Are there easily identifiable personality traits associated with giftedness? What is the link between intense creativity and madness? These are just some of the questions explored in Genius and the Mind. With historical studies of some of the most famous creative people, this exciting book considers the nature of creativity and genius from a psychological standpoint. Chapters, written by leading researchers in the study of genius, span the range of approaches used to understand the subject--from discussions of the role of genes in giftedness to the importance of social context in defining and acknowledging creativity. Mozart's precocity, Byron's mania, Shakespeare's literary brilliance, personalities of the Italian Renaissance painters, and the psychoses of many celebrated writers are all discussed, making this a fascinating text for anyone with an interest in the psychology of genius and geniuses, as well as for students and researchers in the field.
Keywords: Music psychology; Genius; Creativity